A vision of Orkut's users: studying this phenomenon through cognitive absorption (Journal of Information Systems and Technology Management, 2011)
This study aims to identify the influence that Cognitive Absorption has on the intention of using Orkut. It happens due to the fact that Cognitive Absorption is related to the state of deep involvement users carry with an individual task, performed with the support of Information Technology (IT); it corroborates the study on this virtual community. Therefore, through descriptive research with a quantitative character and with the aid of structural equations, 645 Orkut users were investigated. After the identification of suitability of all indexes tested and fit for both constructs and the final model. The conclusion drawn is that Cognitive Absorption explains the 41% intention of using Orkut, emphasizing that for this kind of IT the Cognitive Absorption seems perfectly adequate to measure the Intention of Use.